An assessment of conflict areas between alien and native species richness of terrestrial vertebrates on a macro‐ecological scale in a Mediterranean hotspot. (4th January 2017) - Carpio, A. J.; Barasona, J. A.; Guerrero‐Casado, J.; Oteros, J.; Tortosa, F. S.; Acevedo, P.
Abstract: Understanding how the diversity of invasive species is geographically distributed and identifying the major drivers of that pattern is a relevant challenge as regards invasion biology. The aim of this paper was, therefore, to identify and characterize those areas colonized by a high number of alien species as a means to provide directional indications that can be used to minimize the potential negative effects that the alien species may have on host ecosystems. This is done by applying spatially explicit predictive modeling in order to explain the diversity of vertebrate alien species in Spain. The relative importance of the different factors was assessed using variation partitioning. Our results showed that the main factor as regards predicting the distribution of alien species was the anthropogenic variable, and that this was followed by abiotic variables. The other significant predictor of alien species was the number of native species, which had a positive relationship with the number of alien species. This accord with the 'the rich get richer' acceptance hypothesis, which predicts a higher number of alien species in areas with high native species diversity. In this study, we detected actual conflict areas (ACAs), which have high‐medium values for the number of both native and alien species. Many of the ACAs identified some overlap with protected areas, which further aggravate the problem as these areas are often the home to endangered species which may be adversely affected by the emergence of alien species. This signifies that eradication, control or mitigation programs should be carried out to reduce the undesirable impact of alien species in these areas. However, other areas of conflict also appeared in unprotected areas near to big cities, where monitoring and preventive measures are necessary to avoid the release of new species and their subsequent spread. Abstract : We established the areas that had a higher risk of being colonized by alien species. We found that antropic and ecogeographical variables were the main factors to explain richness of alien species. Urban land uses and the distances to big cities were key features to predict the distribution of alien species. We also identified potential conflict areas, which have higher values for the number of both native and predicted alien species.